Metabolic Syndrome - Shafeeq, Noorhan Khalid; Hussein, Tamara Ala’a; Abass, Eiman AA. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2021)
Metabolic syndrome (MetS) is a combination of health disorders that mainly result from overweight and obesity. It increases the risk of developing cardiovascular disease and diabetes. (MetS) closely related to the existence weight gain or Obesity and laziness. It increases the serum levels of TNF-Î± and change the levels of a number of other parameters (e.g., adiponectin, resistin, and PAI-1). TNF-Î± dose not only appear to cause the production of inflammatory cytokines. It can trigger cell signaling by interacting with TNF-Î± receptors that can lead to insulin resistance. Usually, the digestive system molders the foods you eat and converts them to glucose. Insulin is an anabolic hormone produced by the pancreas that aids glucose get in your cells. To be utilize, as an energy source .Cells do not respond to insulin normally, and sugar cannot easily enter cells in people with insulin resistance. As outcome, blood glucose rises, until the body produces more insulin in an attempt to lower blood sugar. The following factors increase the chance of developing MetS as age increases the risk of developing MetS with age and ethnicity. In the United States, it appears that women of Mexican descent are more likely to develop MetS. Obesity carrying an extra amount of weight, especially in the abdomen, increases the risk of MetS. From this review, it stated that metabolic syndrome stands for the constellation of cardiovascular risk factors that raise the risk of cardiovascular arteriosclerosis and type 2 diabetes. Type 2 diabetes is a major global public health issue with more than 300 million people projected in 2025.